The Role of High-Flow Nasal Oxygen Therapy (HFNOT) in Emergency Medicine: Efficacy and Clinical Applications - Szymon Cholewiński; Marcin Ciechański; Edyta Witkowska; Klaudia Wilk; Bernadetta Wilk; Piotr Stachura; Aleksandra Kasprzyk; Katarzyna Pszczoła; Katarzyna Jurkiewicz; Piotr Rejman (Journal of Education, Health and Sport, 2025)
Introduction: High-Flow Nasal Oxygen Therapy (HFNOT) is an increasingly utilized respiratory support modality in emergency medicine. It offers advantages over conventional oxygen therapy (COT) and non-invasive ventilation (NIV), including enhanced oxygenation, patient comfort, and physiological benefits. Despite growing interest, questions remain regarding its optimal use and effectiveness across different clinical scenarios.